(untitled) (Research, Society and Development, 2022)
Microvessels are small and thin capillaries that develop in the skin, usually of a purplish or reddish color, their caliber varies from 1mm to 2mm, most often affects females and can be caused by genetic factors, obesity, pregnancy, diabetes. and even for spending a lot of time standing, even though they are small-caliber vessels, they can cause aesthetic discomfort and turn into varicose veins, thus causing future health problems. The PEIM, which is the Injectable Aesthetic Procedure for Microvessels, has as main objective to eliminate the small vessels that undergo intradermal dilatation in the lower limbs, this elimination of vessels has a mechanism of action through a sclerosing substance, which is 50% hypertonic glucose. and 75% used in the area of ​​aesthetic Biomedicine to perform the procedure, glucose 75% presents positive results for the elimination of microvessels from the first session, while the use of glucose 50% requires a greater number of sessions of the procedure to present its results, as with any aesthetic procedure, complications can occur in PEIM, such as hyperchromias and even necrosis, which can be recurrent from the excessive use of injected medication. According to studies, the procedure is considered satisfactory and effective and, like other experiments, the result is individual, being often necessary to repeat the application, the two concentrations of glucose are effective and no significant change was observed in the blood glucose of patients who underwent this procedure.